2021
DOI: 10.3390/brainsci11020265
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation in Neurological Physiotherapy: A Systematic Review

Abstract: This systematic review was carried out to compile and assess original studies that included economic evaluations of neurological physiotherapy interventions. A thorough search of PubMED, Cochrane and Embase was developed using keywords such as health economics, neurological physiotherapy and cost analysis, and studies published during the last six-year term were selected. A total of 3124 studies were analyzed, and 43 were eligible for inclusion. Among the studies analyzed, 48.8% were interventions for stroke p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
4
0
1
Order By: Relevance
“…Several studies have already demonstrated that physiotherapists offer treatments worth the money [ 7 , 8 ]. One review provides an overview of economic evaluations for treatments of neurological conditions offered by physiotherapists [ 9 ] and another review evaluates the cost-effectiveness of physical exercise, which is one of the treatment modalities offered by physiotherapists, for various health conditions [ 10 ]. However, an overview of existing economic evaluations of different physiotherapeutic treatment modalities for patients with musculoskeletal conditions is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already demonstrated that physiotherapists offer treatments worth the money [ 7 , 8 ]. One review provides an overview of economic evaluations for treatments of neurological conditions offered by physiotherapists [ 9 ] and another review evaluates the cost-effectiveness of physical exercise, which is one of the treatment modalities offered by physiotherapists, for various health conditions [ 10 ]. However, an overview of existing economic evaluations of different physiotherapeutic treatment modalities for patients with musculoskeletal conditions is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond loss of mobility, stroke-induced disability takes a societal toll; many stroke survivors can no longer contribute to the workforce and lose their functional role in their community [ 2 ]. They often enter a downward spiral that is associated with a steep decline in their psychological and cognitive well-being, affecting their families and social circles [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of economic evaluations of neurological physiotherapeutic interventions has addressed this challenge. 6 In contrast to standard systematic reviews that article only provides an overview of existing studies, based on their geographical location and underlying health condition in the neurological physiotherapeutic field. Unfortunately, the quality of the included studies was not evaluated, which would have provided valuable insights on the quality of the evidence and the research gaps.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of economic evaluations of neurological physiotherapeutic interventions has addressed this challenge 6. In contrast to standard systematic reviews that article only provides an overview of existing studies, based on their geographical location and underlying health condition in the neurological physiotherapeutic field.…”
Section: Introductionmentioning
confidence: 99%